Pengembangan Perangkat Pembelajaran Fisika Kelas X Dengan Model Plomp Di Sma Negeri 5 Palu - Kusnaeni Kusnaeni; Marungkil Pasaribu; I Komang Werdhiana (Universitas Tadulako, 2017)
The research aims at developing the Physics subject Instructional packages of year X semester I SMAN 5 Palu by Plomp model. The research employed Research Development Desain. The instructional package drafis that have been previously developed validated by a content expert, a design expert, and a media expert. The revised version of the packages were tried out info three defferent subject indimall group and big group which contained 30 student and 1 teacher. Questionnaire designed in 1 to 5 scale was used as the instrument of data collection. Suggestion, input and coment during consultation period were also noted and used to compliment the collected data from the questionnaire. The results of the data analysis show that 1) the instructional materials product score ranges from 75.38% to 96.84%, indicating that the instructional material is Good and Very Good qualifying , 2) The teacher’s book product score ranges with the average of 80% indicating that the teacher’s book product is Good qualifying , and 3) The s student’s book product score ranges from 80% to 96% indicating that the student’s book product is Good and Very Good qualifying. Based on product feasibility assessment table, that if the cumulative result of the calculation to the development of products derived reach the criteria above a value of 75%, the products developed are considered valid and reliable for use. The effectiveness of the instructional materials obtained by t-test which was tcounted(2,675) , t table(0,05:58)(1,675). It implies that the instructional packages have been valid and ready to be used.